JUAL BELI DROPSHIPPING DALAM TINJAUAN HUKUM ISLAM - Muh. Akbar (Hukum Ekonomi Syariah, Fakultas Syariah, IAIN Palopo, 2020)
The research seeks to obtain and describe data regarding the sale and purchase of dropshipping in Islamic law. Research Results: 1) In practice, the buyer transfers a certain amount of money in cash then from the money the dropshipper buys the goods to the agent, then the agent will send the goods but the delivery not on behalf of the agent but on behalf of the dropshipper because the product actually owned by the dropshipper. 2) Online dropshipping trading transactions according to Islamic law are permitted as long as they meet the principles and requirements of the sale and purchase, until there was a special argument that prohibits the transaction in Islam. The rule of law of muamalah in Islam was permissible as long as there was an argument or nash of shari that prohibits the muamalah, dropshipping trading does not violate sharia provisions. 3) Advantages of buying and selling through online dropshipping transactions. Buying and selling dropshipping online can boost sales of more products to buyers through existing marketers. There are several disadvantages or drawbacks to the dropshipping business owner, namely: The risk for a dropshipping owner was a bet because marketers can over-claim their products. Research implications that the author can convey in this study are several ways of online business that can be compared with dropshipping: Providing procurement services. So the seller can offer services to others for the procurement of the goods they need. Become an authorized agent and distributor.